Complementary strategies in pancreatic cancer precision medicine: therapeutic prediction and immune modulation - Lee, Wonmin; Woo, Hyun-Myung; Cho, Ja Hyang; Kim, Man S. (Frontiers in Oncology, 2025)
BackgroundPancreatic ductal adenocarcinoma (PDAC) remains highly lethal with five-year survival below 10%, primarily due to late diagnosis, treatment resistance, and immunosuppressive microenvironment.MethodsThis review examines recent advances in PDAC precision medicine by analyzing organoid-based drug screening platforms, mRNA immunotherapy developments, and integrated diagnostic technologies.ResultsPatient-derived organoids demonstrate strong predictive value for clinical outcomes, with drug sensitivity profiles correlating with patient responses (concordance >80%). Personalized mRNA neoantigen vaccines induce robust T-cell responses, with vaccine responders showing significantly prolonged recurrence-free survival (median not reached vs. 13.4 months). KRAS-targeted therapies achieve 10-15% response rates in G12C-mutant PDAC. Integration of spatial transcriptomics and liquid biopsy enables real-time molecular monitoring.ConclusionsThe development of patient-derived organoids for drug sensitivity testing, personalized mRNA vaccines for immune activation, and precision diagnostic and therapeutic technologies represents complementary advances in PDAC. While each approach has demonstrated independent clinical value, their integration remains an important future direction that may provide a comprehensive framework for improving outcomes in PDAC.